15N-Leucine: Health benefits, applications and issues related to ileal endogenous amino acid losses in poultry. Issue 1 (1st March 2017) - Soomro, R.N.; Yao, J.; Abd El-Hack, M.E.; Abbasi, I.H.R; Hu, R.; Saeed, M.; Arain, M.A.; Soomro, S.A.; Yang, X.; Fowler, J.; Alagawany, M.
Abstract : Having accurate data for ileal amino acid digestibility of a feed ingredient is one of the ways to enhance protein and nitrogen utilisation, improve poultry feeding efficiency, and mitigate ammonia emission and pollution in the environment. Moreover, the precise estimation of endogenous amino acid losses (EAAL) depends on formulating diets on digestible amino acid (DAA) basis. Numerous methods have been reported to determine the endogenous fractions including the regression method, the protein-free diet, and the total digestible nitrogen diet. The EAAL determined by these techniques can help in calculated corrected values for amino acid digestibility, termed true digestibility. Certain dietary components that can be called 'specific losses' could lead to higher losses than the basal calculation would indicate. To determine the basal plus specific losses (total endogenous losses), some researchers suggested the 15 N-dilution method, which allows the determination of the actual digestibility. This method needs more studies and evaluations because there are some controversial issues about this methodology, such as the validity of the 15 N-dilution technique when applied to any amino acid or to total nitrogen, the reference pool for the estimation of the labelling of endogenous fractions/secretions, anti-nutritional agents, the effect of bird age, mucin, different cereal grains, as well as the marker itself and the proper assessment. This review will be focused on the above issues, finding that the recently reported 15 N isotopes single injection method could be an easy, time-saving, consistent, and reliable methodology for EAAL estimation in poultry.